Anti-poverty policies analysis for rural households in Iran: a system dynamics approach. (30th June 2021) - Nahavandi, Nasim; Ajayebi, Seyed Mohamad Baghe
Nowadays, poverty is one of the main problems in human societies. Poverty dynamics can help to predict the poverty trend in the future, and this can assist policymakers in making new policies to eradicate poverty. The purpose of this paper is to develop a new system dynamics model for the poverty of rural households to analyse anti-poverty policies in Iran. The proposed system dynamics model is used for analysing the anti-poverty policies and predicting their effects on poor households. This model is validated by data from rural households supported by relief foundation (RF) in Iran. Five different policies have been considered for these households to find which policy has a sustainable effect on rural household income. The model results show supporting households in non-financial aid programs have a sustainable impact on their income and eradicate poverty faster than financial aid programs. Teaching the environmental aspects of sustainable development goals like soil management and providing fertiliser for them affect soil fertility and provide more crop for them.